The Effectiveness of the Mind Mapping Technique in Improving Students' Ability to Organize Ideas in Writing Descriptive Texts - Pebriani, Eti Nurhidayati; Sujana, I Made; Zamzam, Ahmad (Journal of Authentic Research, 2025)
This study investigates the effectiveness of the Mind Mapping technique in improving junior high school students’ ability to organize ideas when writing descriptive texts at one of the public Islamic schools in West Lombok. A quasi-experimental design was used, consisting of two groups of seventh-grade students: an experimental group that received instruction through Mind Mapping and a control group that was taught using conventional methods. Before the treatment, students’ initial writing ability was relatively low, as indicated by the pre-test mean score of 60.25, showing limited skills in organizing ideas clearly and coherently. Mind Mapping, defined in this study as a visual technique that helps students generate, connect, and structure ideas through branching diagrams starting from a central concept, was applied over three instructional sessions using the Right Column Mind Map. Data were obtained from pre-test and post-test activities involving writing tasks describing a person and analyzed using an independent samples t-test in SPSS 31, including normality and homogeneity tests, to determine the significance of differences between the two groups. The findings indicated that the experimental group experienced a notable improvement, with their mean score increasing from 60.25 on the pre-test to 79.42 on the post-test—an overall gain of 19.17 points. Meanwhile, the control group’s improvement was limited to 10.41 points. The independent samples t-test showed that this difference was statistically significant (p = .001 < .05). A further analysis revealed that Mind Mapping improved three aspects of idea organization: unity (maintaining focus on the central idea), completeness (expanding relevant supporting details), and coherence (ensuring logical sequencing and smooth transitions between ideas). Thus, the null hypothesis (H?), which stated that Mind Mapping does not significantly enhance students’ ability to organize ideas, was rejected. In contrast, the alternative hypothesis (H?) was accepted. These findings imply that teachers can adopt Mind Mapping as an effective pre-writing strategy to help students plan and organize ideas more systematically, thereby supporting the objectives of the Merdeka Curriculum in fostering creativity, critical thinking, and structured writing.